Clear cell variant of calcifying epithelial odontogenic tumor: an unusual case report - Mezzomo Faccin, Kallana; Stähelin, Heron; Pires Claudio, Thiago; Cristina Trentin Bordignon, Natalia; Riet Correa Rivero, Elena; Luiz Cavalcanti Albuquerque-Junior, Ricardo; Gondak, Rogerio (Journal of Oral Diagnosis, 2025)
The calcifying epithelial odontogenic tumor (CEOT), also known as Pindborg tumor, is a rare odontogenic neoplasm originating from epithelial tissue. The presence of clear cells within CEOT is an unusual finding, indicating a variant with distinctive histopathological features and possible clinical implications. This study presents a case report of a clear cell variant of CEOT in a 36-year-old male patient with painless swelling in the anterior mandible. The occurrence of clear cells in CEOT is uncommon and may mimic other clear cell tumors. Therefore, the identification of amyloid-like deposits and calcifications is essential in confirming the diagnosis of clear cell variant of CEOT.